Genomic Analyses of Unveil Helmeted Guinea Fowl (Numida meleagris) Domestication in West Africa. (1st May 2021) - Shen, Quan-Kuan; Peng, Min-Sheng; Adeola, Adeniyi C; Kui, Ling; Duan, Shengchang; Miao, Yong-Wang; Eltayeb, Nada M; Lichoti, Jacqueline K; Otecko, Newton O; Strillacci, Maria Giuseppina; Gorla, Erica; Bagnato, Alessandro; et al.
Abstract: Domestication of the helmeted guinea fowl (HGF; Numida meleagris ) in Africa remains elusive. Here we report a high-quality de novo genome assembly for domestic HGF generated by long- and short-reads sequencing together with optical and chromatin interaction mapping. Using this assembly as the reference, we performed population genomic analyses for newly sequenced whole-genomes for 129 birds from Africa, Asia, and Europe, including domestic animals ( n  = 89), wild progenitors ( n  = 34), and their closely related wild species ( n  = 6). Our results reveal domestication of HGF in West Africa around 1, 300–5, 500 years ago. Scanning for selective signals characterized the functional genes in behavior and locomotion changes involved in domestication of HGF. The pleiotropy and linkage in genes affecting plumage color and fertility were revealed in the recent breeding of Italian domestic HGF. In addition to presenting a missing piece to the jigsaw puzzle of domestication in poultry, our study provides valuable genetic resources for researchers and breeders to improve production in this species.